The Humanities in Scandinavian Welfare States: A comparison of argumentation and knowledge policies of the Danish, Norwegian, and Swedish Research Councils in the mid 1980s - Eckhardt Larsen, Jesper (Revista Española de Educación Comparada, 2024)
A comparison of national policies towards the humanities in the three Scandinavian countries, Denmark, Sweden, and Norway show surprisingly large differences. However, similarities exist between the cases. All three countries can be characterized as small, with strong traditions of state intervention in all areas of society, and with a high trust in the state apparatus. They were all comparatively early in establishing national research councils after WWII also supporting the humanities. In the period from WWII till the 1980s national knowledge cultures (Knorr Cetina) in Denmark and Norway designated the humanities to both preserve and renew ‘culture’. The national impetus being strongest in Norway. In contrast a modern narrative of cultural discontinuity has dominated in Sweden. In the Swedish case the national knowledge culture has had difficulty in reconciling the humanities with modern democracy. Here the humanities have been understood as conservative and even antidemocratic.